Modelling of hydrodynamics in Airlift reactor - Nur Hazieqah, Kahil (2013)
Airlift reactors are widely used in chemical, petrochemical and biochemical industries. This type of reactor is much more productive in terms of specific power demands and commercial scale-effectiveness. Concept of hydrodynamics in airlift reactors is influenced by these two parameters; axial gas velocity and axial liquid velocity. It is important to understand the concept as the parameters affected to all aspects in performance of airlift reactors. Study of hydrodynamics has been started since decades ago, but experimental study is not a first choice for the research due to an expensive setup to develop. Experimental study using Computer Automated Radioactive Particle Tracking (CARPT) and Laser Doppler Anemometry (LDA) are examples of experimental study on airlift reactors. Basically, these experimental study take lots of times to scale-up the prototype and costly. Thus, Computational Fluid Dynamics (CFD) is used as an alternative method as the cost for the study is much cheaper and even better in performing the result. GAMBIT 2.2 and FLUENT 6.3 are used to evaluate the performance of airlift reactors. Several phases involved in this study by suing two Eulerian models; mixture k-ԑ model and two phase k-ԑ model. The experimental literature from Van Baten et al. (2003) is chosen as the validation data for CFD simulation. The CFD predicts the axial component of gas velocity and axial component of liquid velocity fairly well, although the results seem to suggest that further improvement need to be studied. It is clear from the modelling exercise performed in this work that CFD is a great method for modelling the performance of airlift reactor.